Characterization of Plasmodium vivax Proteins in Plasma-Derived Exosomes From Malaria-Infected Liver-Chimeric Humanized Mice - Gualdrón-López, Melisa; Flannery, Erika L.; Kangwanrangsan, Niwat; Chuenchob, Vorada; Fernandez-Orth, Dietmar; Segui-Barber, Joan; Royo, Felix; Falcón-Pérez, Juan M.; Fernandez-Becerra, Carmen; Lacerda, Marcus V. G.; Kappe, Stefan H. I.; Sattabongkot, Jetsumon; et al. (Frontiers in Microbiology, 2018)
Exosomes are extracellular vesicles of endocytic origin containing molecular signatures implying the cell of origin; thus, they offer a unique opportunity to discover biomarkers of disease. Plasmodium vivax, responsible for more than half of all malaria cases outside Africa, is a major obstacle in the goal of malaria elimination due to the presence of dormant liver stages (hypnozoites), which after the initial infection may reactivate to cause disease. Hypnozoite infection is asymptomatic and there are currently no diagnostic tools to detect their presence. The human liver-chimeric (FRG huHep) mouse is a robust P. vivax infection model for exo-erythrocytic development of liver stages, including hypnozoites. We studied the proteome of plasma-derived exosomes isolated from P. vivax infected FRG huHep mice with the objective of identifying liver-stage expressed parasite proteins indicative of infection. Proteomic analysis of these exosomes showed the presence of 290 and 234 proteins from mouse and human origin, respectively, including canonical exosomal markers. Human proteins include proteins previously detected in liver-derived exosomes, highlighting the potential of this chimeric mouse model to study plasma exosomes derived unequivocally from human hepatocytes. Noticeably, we identified 17 parasite proteins including enzymes, surface proteins, components of the endocytic pathway and translation machinery, as well as uncharacterized proteins. Western blot analysis validated the presence of human arginase-I and an uncharacterized P. vivax protein in plasma-derived exosomes. This study represents a proof-of-principle that plasma-derived exosomes from P. vivax infected FRG-huHep mice contain human hepatocyte and P. vivax proteins with the potential to unveil biological features of liver infection and identify biomarkers of hypnozoite infection.